El Direccionamiento Estratégico de las IES en el Ecuador Apalancado en las TIC. Caso: Universidad Estatal De Milagro - Vinueza-Martínez, Jorge (Ciencia UNEMI, 2013)
Today the Higher Education Institutions (HEIs) from Ecuador and other Latin American countries lack, within the administration, a basic methodology that promotes the development, measurement, control and monitoring standardized, short, medium and long term , Institutional Plans. This creates the need to design and implement a Strategic Management Model and Operational Miracle State University, UNEMI, as part of the Integrated Planning as standardized assessment and learning is a process that must reflect intrinsic outcome quality, based on measurable objectives and initiatives, and obtained by measurement techniques to quantify the achievement of the objectives. It also reveals the lack of definition of ICT-based processes and information systems that optimize the monitoring and control of programs and projects. The evaluation and monitoring are fundamental strategic direction to measure the achievement of results, without planning support tools, such as: POA [Annual Operating Plan], PAT [Annual Technology Plan], PAC [Annual Procurement Plan], PAI [Annual Investment Plan], it is difficult to accurately quantify the level of performance of this institution.